Ecological Associations Between Inclusionary Zoning Policies and Cardiovascular Disease Risk Prevalence: An Observational Study. Issue 9 (September 2021) - Jones, Antwan; Squires, Gregory D.; Nixon, Carolynn
Abstract : Background: Providing an adequate supply of affordable housing has become an increasingly difficult challenge for US cities. Inclusionary zoning (IZ) policies have become an increasingly popular response. Substantial research has demonstrated the health benefits of stable, affordable housing. There is anecdotal but not systematic evidence that IZ policies may be associated with some health benefits of affordable housing. Methods: We rely on data from the 2017 500 Cities Project, the 2016 to 2017 Lincoln Institute for Land Policy survey, and the 2011 to 2015 American Community Survey. We perform bivariate tests and cluster ordinary least squares regression to examine associations at the municipal level between having inclusionary zoning (IZ) policies, the attributes of those policies, and the prevalence of several cardiovascular outcomes. Results: Cardiovascular outcomes and socioeconomic characteristics were uniformly better in cities with IZ policies. IZ policies were associated with lower blood pressure (95% CI, −0.50 to −0.13), cholesterol (CI, −0.89 to −0.31), and blood pressure medication (CI, −0.57 to −0.03) prevalence. Some characteristics of IZ programs such as being mandatory, prioritizing rental development, and allocating a larger share of affordable housing are associated with cardiovascular risk prevalence. Conclusions: Characteristics of IZ programs that ultimately benefit low-income residents are associated with favorable municipal-level cardiovascular health. Further, IZ policies could potentially address complex health challenges among economically vulnerable households. Abstract : Supplemental Digital Content is available in the text.